Co-transport of gold nanospheres with single-walled carbon nanotubes in saturated porous media. (1st August 2016) - Afrooz, A.R.M. Nabiul; Das, Dipesh; Murphy, Catherine J.; Vikesland, Peter; Saleh, Navid B.
Abstract: Porous media transport of engineered nanomaterials (ENMs) is typically assessed in a controlled single-particulate environment. Presence of a secondary particle (either natural or engineered) in the natural environment though likely, is rarely taken into consideration in assessing ENMs' transport behavior. This study systematically assesses the effect of a secondary ENM (i.e., pluronic acid modified single-walled carbon nanotubes, PA-SWNTs) on a primary particle (i.e., gold nanospheres, AuNSs) transport through saturated porous media under a wide range of aquatic conditions (1–100 mM NaCl). AuNS hetero-dispersions (i.e., with PA-SWNTs) are transported through saturated sand columns, and the transport behavior is compared to AuNS-only homo-dispersion cases, which display classical ionic strength-dependent behavior. AuNS hetero-dispersion, however, is highly mobile with little to no ionic strength-dependent effects. This study also assesses the role of pre-coating of the collectors with PA-SWNTs on AuNSs' mobility, thereby elucidating the role played by the order of introduction of the secondary particles. Pre-existence of the secondary particles in the porous media shows enhanced filtration of primary AuNSs. However, the presence of natural organic matter (NOM) slightly increases AuNS mobility through PA-SWNT coated sand at 10 mM ionic strength. The study results demonstrate that the presence and order of addition of the secondary particles strongly influence primary particles' mobility. Thus ENMs can demonstrate facilitated transport or enhanced removal, depending on the presence of the secondary particulate matter and background solution chemistry. Graphical abstract: Highlights: Co-transport of gold nanospheres (AuNSs) was investigated for the first time. AuNS co-transport was influenced by the presence of single-walled-carbon nanotubes (SWNTs). AuNS in hetero-dispersion demonstrated enhanced mobility via facilitated transport. AuNS mobility in SWNT-coated sand was limited due to preferential deposition on the coated sand. At fresh pore-water scenario, natural organic matter had minor influence on the AuNS co-transport.